Financial communications : information processing, media integration, and ethical considerations - Wang, Shih-Lun Alex (New York Palgrave Macmillan, 2013)
Financial Communications showcases why it is crucial for financial institutions to enhance key communication processes, rebuild trust with its customer base, improve relationships, and derive better brand awareness amongst key stakeholders within the industry.
Includes bibliographical references (pages 189-220).
aia 24/10/17
Keywords: Financial disclosure; Financial services industry--Communication systems; Financial services industry--Information services